Silencing of GATA3 defines a novel stem cell-like subgroup of ETP-ALL - Fransecky, Lars; Mossner, Maximilian (Journal of hematology & oncology, 2016)
GATA3 is pivotal for the development of T lymphocytes. While its effects in later stages of T cell differentiation are well recognized, the role of GATA3 in the generation of early T cell precursors (ETP) has only recently been explored. As aberrant GATA3 mRNA expression has been linked to cancerogenesis, we investigated the role of GATA3 in early T cell precursor acute lymphoblastic leukemia (ETP-ALL).
Gesehen am 06.08.2019